22 Tapijten. - Borngräber, Christian; Britsch, Eckart; D'haeseleer, Hilde; Daenens, Lieven; Hobl-Friedrich, Mechtild; Ludwig, Andreas; Pott, Karin; Strobel, Ingo; Walgrave, Jan; Weinand, Herbert Jakob; Museum voor Sierkunst Gent; Haus am Lützowplatz, Berlin; et al. (Gent : Museum voor Sierkunst Gent, 1995)
Aerts, Leo ; Bouttens, Philippe ; De Buck, Siegfried ; Dessauvage, Tjok ; Dewulf, Koenraad ; Mestdagh, Chris ; Moerman, Piet ; Van Schuylenbergh, André ; Vermeersch, José ; Vermeersch, Rik ; Weyers & Borms ; Albus, Volker ; Bach, Elvira ; Dehne, Pia ; Frenzel, Hanne ; Hajek, Katja ; Hornemann, Thomas ; Salomé ; Skoda, Claudia ; Brevern, Renate Von ; Weinaud, Herbert Jakob ; Zimmer, Bernd
biografie
Duits
Engels
Nederlands
22 Tapijten/Carpets/Teppiche, Museum voor Sierkunst, Gent, 29.9.1995 - 4.11.1995 / Haus am Lützowplats, Berlin, 18.2.1996 - 7.4.1996 / Städtische Galerie Sammlung Ostdeutscher Kunst, Eisenhüttenstadt, 19.1.1996 - 11.2.1996
boek